Practices for no-tillage in an improved cerrado area: Emergence, survival and initial growth of forest species - Gianluppi, Daniel; Smiderle, Oscar José; Souza, Aline das Graças; Maia, Sonicley da Silva (Seven Editora, 2023)
Considering that research on survival and growth of forest species via no-tillage in the improved cerrado of Roraima is still scarce, this research adds information to this technique with six forest species regarding emergence, survival and increase in height and diameter of plants over 18 months. In view of the above, the objective was to indicate procedures for direct sowing of tree forest species (pau-rainha, maçaranduba, freijó, jatobá, itaúba and African mahogany) in a cerrado area of Roraima, with the use of shrubby legumes, as a way to dispense with the formation and management of seedlings in nursery and allow the establishment of forest plantations with reduced costs. Thus, in the experimental area each species, maçaranduba, freijó, jatobá, itaúba, pau-rainha and African mahogany in July 2021 were sown every 50 cm apart, in the row and distributed two seeds at a depth of up to 1 cm according to the size of the seed. The experiment occupied a total area of 4,500 m2 and a useful area with seeds sown of 3,456 m2, totaling 648 seeds per species. The percentage of emergence was evaluated at 120 days after sowing, and seedling survival after 6, 12 and 18 months. In addition, the increments in height and diameter were evaluated from 6 to 12 months and from 12 to 18 months. Of the six forest species studied, 2% (pau-rainha), 6% (African mahogany) and 53% (jatobá) of seedling emergence presented with 2% (pau-reira), with survival >80% after 18 months. In the same period, African mahogany and queen's wood had a survival rate of 50%. Direct sowing in the improved cerrado from Roraima to Jatobá is recommended. The procedure used to promote the increase in stem diameter (ΔDC) of jatobá plants from no-tillage via seeds from six to 18 months is the application of 3.0 t ha-1 of limestone and 1.8 t ha-1 of agricultural gypsum in the cerrado of Roraima, being an appropriate species for the establishment of forest plantations with costs of 1.55 reais per seedling.DOI:https://doi.org/10.56238/uniknowindevolp-020